Identifikasi Penentu Intensi Studi di Perguruan Tinggi: Studi Kasus terhadap Universitas Swasta Katolik di Indonesia - Alexander Joseph Ibnu Wibowo; Yohanes Eko Widodo (Universitas Kristen Maranatha, 2013)
The main objective of this study is to identify the variables or factors determining the intention to study to the university. This study was designed as a quantitative research through a survey. A total of 1979 new students were included in the study. They came from seven faculties of a Catholic private university inIndonesia. Using exploratory factor analysis technique, we successfully identified nine constructs influencing the intention of students to study to the university. Valuable contribution of this study is the finding of nine constructs above, namely:social status, assistance in financing of the study, university image, campus convenience, achievement motivation, values of life, motivation to work, perceived quality of graduates, and the perceived quality of teaching. The findings of this study are very helpful especially for university marketer to monitor those ninefactors constinuously. These findings also help university marketer in designing various marketing programs effectively.Keywords: Intention to Study, Marketing, Exploratory Factor Analysis, Higher Education, Indonesia